Tanggung Jawab Korporasi Dinas Kebersihan Atas Pengelolaan Sampah Berdasarkan Undang-Undang No. 18 Tahun 2008 Tentang Pengelolaan Sampah - Jennifer Jennifer; Alvi Syahrin; Madiasa Ablisar; Suhaidi Suhaidi (Universitas Sumatera Utara, 2019)
Abstract. Garbage is one of the environmental problems that become global problems that have not had a way out. In Indonesia alone, waste management that carried out by the Department of Sanitation has not been successfully implemented waste management in accordance with quality standards that have been set in the legislation. The waste management causes environmental pollution and hazards to public health. This is the importance of waste management and the regulation that regulate it. The Sanitation Department as the public sector who carry out the tasks assigned by the Regional Government in accordance with the Law No.18 of 2008. In this corporate accountability, accountability is divided into accountability of attendance, accountability of the board, or corporation and Board accountability. In corporate liabilities in public places such as the Sanitation Department, the State acts as a legal entity. The responsible board is determined by determining who directs the mind and has the authority to implement or prevent the follow-up imposed by the law. Keywords : waste management, corporate liabilities